A development of modest proportions: the application of the principle of proportionality in the Targeted Killings Case - Kohen, ʿAmiḥai (Journal of international criminal justice, 2007)
The comment critically discusses the application of the principle of proportionality by the Israeli Supreme Court in the Targeted Killings case. While the judgment confirms the customary status of the principle and its applicability to all Israel Defense Forces (IDF) military operations during armed conflicts, its substantive contents remain, as might have been expected, unclear. In particular, the application of the least-injurious alternative subtest with regard to all civilians taking a direct part in hostilities is unsubstantiated and perhaps too sweeping. However, the reference by the Court to ex ante and ex post review mechanisms to monitor the application of the proportionality principle constitutes a positive contribution to its development under international humanitarian law, which might also have some implications for criminal prosecutions of soldiers and commanders involved in unlawful targeted killing operations